Growth of Bio-Fuel Literature: A Analytical Study - Arya, Harsh Bardhan; Mishra, J. K. (Journal of Information and Knowledge, 2011)
This study carried out an analysis of the literature on Bio-fuel. The purpose was to study the periodic growth of literature, distribution of authorship, distribution of subject, bibliographical forms of literature, productivity ranking, and geographic origin of literature on the subject. Data was collected through physical verification of both primary and secondary sources of information. This data set was analyzed using various bibliographic characteristics. The findings show the increase in the literature bio-fuel since 1971 and USA, the leading country in undertaking Bio-fuel research. Most of the literature comes from Bio-diesel and Alcohol fuel. The geographical distribution shows that USA and India are the leading contributors to this literature.